2020
DOI: 10.1016/j.heliyon.2020.e03858
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and characterization of chitinase produced by Bacillus licheniformis B307

Abstract: The optimal conditions required for chitinase production from Bacillus licheniformis B307 strain, obtained from Syrian soil, were studied. Optimization experiments were carried out under submerged fermentation conditions, and colloidal chitin was the source of carbon. Luria broth medium supplied with 0.5% colloidal chitin was the optimum medium for chitinase production. The maximum chitinase yield was obtained at 30 C, pH6, incubation time 14 days, and 150 rpm. The optimum chitinase activity was achieved at 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 36 publications
1
29
2
Order By: Relevance
“…Compared to Gram-positive bacteria, 90% of the diversity of Gram-negative bacteria in marine ecosystems has traits that enhance survival of these organisms in extreme temperature, tolerance and rapid adaptation to nutrient deficiencies, and high salt concentration [ 33 , 34 ]. The chitinase activity of the mutated strains of UV-11 and EMS-13 showed values greater than earlier reports [ 27 ] with a maximum specific enzymatic activity of 14.2 U/mL in a strain of Bacillus licheniformis B307. On the other hand, our wild strain of Bacillus licheniformis SSCL-10 showed chitinolytic activity values of 3.4 U/mL, which is lower than the mutant values compared in this study and reported in our earlier studies [ 7 ].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Compared to Gram-positive bacteria, 90% of the diversity of Gram-negative bacteria in marine ecosystems has traits that enhance survival of these organisms in extreme temperature, tolerance and rapid adaptation to nutrient deficiencies, and high salt concentration [ 33 , 34 ]. The chitinase activity of the mutated strains of UV-11 and EMS-13 showed values greater than earlier reports [ 27 ] with a maximum specific enzymatic activity of 14.2 U/mL in a strain of Bacillus licheniformis B307. On the other hand, our wild strain of Bacillus licheniformis SSCL-10 showed chitinolytic activity values of 3.4 U/mL, which is lower than the mutant values compared in this study and reported in our earlier studies [ 7 ].…”
Section: Discussioncontrasting
confidence: 77%
“…The crude enzyme was partially purified from the culture supernatant (wild, UV mutant, and EMS mutant strains) using 65% saturated ammonium sulfate (SAS) precipitation at 4°C in stirring according to the method of Akeed et al [ 27 ]. Precipitation was done by centrifuging at 11,500 x g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the expression of chitinases from Serratia marcescens PRNK-1 [ 18 ], Pedobacter sp. PR-M6 [ 19 ], and Bacillus licheniformis B307 [ 20 ] were incubated in 0.5% (w/v) colloidal chitin. Chitinases from Acremonium sp.…”
Section: Resultsmentioning
confidence: 99%
“…In silico studies of both β-1,3-glucanase and chitinase proteins from bacteria, fungi and different plants have been reported [12,[15][16][17]. However, there is a lack of in silico characterization and molecular interactions of both β-1,3-glucanase and chitinase proteins from wheat and their respective ligands in literature.…”
Section: Introductionmentioning
confidence: 99%